Predictors of blood pressure among adults: the role of lifestyle and body composition - Evelin Malinti; Yunus Elon; Mori Agustina br Perangin-angin (International Journal of Public Health Science (IJPHS), 2026)
Hypertension is influenced by multiple biological and behavioral factors; however, the relative contributions of body age and body composition remain unclear. This study examined the associations of lifestyle behaviors, body age, and body composition with blood pressure among 167 adults in Indonesia using a cross-sectional design. Lifestyle score, body age, body mass index (BMI), skeletal muscle mass, total body fat percentage, and blood pressure were assessed using standardized procedures. Spearman correlation and multiple linear regression analyses were performed. Body age was the only significant predictor of systolic blood pressure (β = .311, p = .002). In contrast, skeletal muscle mass (β = .172, p = .030) and total body fat percentage (β = .248, p = .017) were significant positive predictors of diastolic blood pressure. Lifestyle score and BMI were not significant predictors in the regression models. These findings suggest that physiological aging and body composition are more strongly associated with blood pressure than lifestyle behaviors. Incorporating body age and body composition assessments into cardiovascular risk screening may improve hypertension prevention and early intervention strategies.